Bioplastic from peel and rind of tropical fruits in Southeast Asia: A mini-review / Wahida Abdul Rahman ... [et al.] - Abdul Rahman, Wahida; Kamaruddin, Muhammad Syafiq; Samsudin, Noradurrah; Azizan, Nur Azfira; Nor Muhammed, Nur Izzati (Research Management Institute (RMI), 2023)
Southeast Asian (SEA) countries have faced numerous challenges in managing their increasing amount of agricultural waste, particularly fruit waste. Fruit waste, like peel and rind, constitutes a substantial portion of total waste generated in SEA countries due to the high consumption of fruits in the region. In addition, inadequate waste management infrastructure, lack of proper disposal methods, and low awareness among the public have exacerbated the problem. The overproduction of plastic waste has become a global environmental issue, and SEA countries are not exempt from this problem. However, using bioplastics made from fruit peel and rind can reduce the dependence on traditional plastics. This paper aims to provide a mini-review regarding bioplastic production from fruit waste (peels and rinds) generated from tropical fruit of SEA countries. Moreover, this minireview aims to evaluate their potential to replace traditional plastics in various industries. One potential method to solve this issue is converting fruit waste into bioplastics, which can provide a sustainable and eco-friendly alternative to conventional plastics. Bioplastics, derived from renewable sources such as fruit waste, are biodegradable, compostable, and can reduce carbon footprint. The findings of this paper indicate that fruit waste from peel and rind is a promising source of raw materials for bioplastic production in SEA countries. Bioplastics' fruit waste properties are comparable to conventional plastics and their applications. Furthermore, using fruit waste for bioplastic production can address the region's waste management issue.